Meta-analysis of 65,734 individuals identifies TSPAN15 and SLC44A2 as two susceptibility loci for venous thromboembolism. - Germain, Marine; Chasman, Daniel I; de Haan, Hugoline; Tang, Weihong; Lindström, Sara; Weng, Lu-Chen; de Andrade, Mariza; de Visser, Marieke C H; Wiggins, Kerri L; Suchon, Pierre; Saut, Noémie; Smadja, David M; et al. (Am J Hum Genet, 2015)
Venous thromboembolism (VTE), the third leading cause of cardiovascular mortality, is a complex thrombotic disorder with environmental and genetic determinants. Although several genetic variants have been found associated with VTE, they explain a minor proportion of VTE risk in cases. We undertook a meta-analysis of genome-wide association studies (GWASs) to identify additional VTE susceptibility genes. Twelve GWASs totaling 7,507 VTE case subjects and 52,632 control subjects formed our discovery stage where 6,751,884 SNPs were tested for association with VTE. Nine loci reached the genome-wide significance level of 5 × 10(-8) including six already known to associate with VTE (ABO, F2, F5, F11, FGG, and PROCR) and three unsuspected loci. SNPs mapping to these latter were selected for replication in three independent case-control studies totaling 3,009 VTE-affected individuals and 2,586 control subjects. This strategy led to the identification and replication of two VTE-associated loci, TSPAN15 and SLC44A2, with lead risk alleles associated with odds ratio for disease of 1.31 (p = 1.67 × 10(-16)) and 1.21 (p = 2.75 × 10(-15)), respectively. The lead SNP at the TSPAN15 locus is the intronic rs78707713 and the lead SLC44A2 SNP is the non-synonymous rs2288904 previously shown to associate with transfusion-related acute lung injury. We further showed that these two variants did not associate with known hemostatic plasma markers. TSPAN15 and SLC44A2 do not belong to conventional pathways for thrombosis and have not been associated to other cardiovascular diseases nor related quantitative biomarkers. Our findings uncovered unexpected actors of VTE etiology and pave the way for novel mechanistic concepts of VTE pathophysiology.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Membrane Glycoproteins; Membrane Transport Proteins; Odds Ratio; Tetraspanins; Venous Thromboembolism

Assessing the causal relationship between obesity and venous thromboembolism through a Mendelian Randomization study. - Lindström, Sara; Germain, Marine; Crous-Bou, Marta; Smith, Erin N; Morange, Pierre-Emmanuel; van Hylckama Vlieg, Astrid; de Haan, Hugoline G; Chasman, Daniel; Ridker, Paul; Brody, Jennifer; de Andrade, Mariza; Heit, John A; et al. (Hum Genet, 2017)
Observational studies have shown an association between obesity and venous thromboembolism (VTE) but it is not known if observed associations are causal, due to reverse causation or confounding bias. We conducted a Mendelian Randomization study of body mass index (BMI) and VTE. We identified 95 single nucleotide polymorphisms (SNPs) that have been previously associated with BMI and assessed the association between genetically predicted high BMI and VTE leveraging data from a previously conducted GWAS within the INVENT consortium comprising a total of 7507 VTE cases and 52,632 controls of European ancestry. Five BMI SNPs were associated with VTE at P < 0.05, with the strongest association seen for the FTO SNP rs1558902 (OR 1.07, 95% CI 1.02-1.12, P = 0.005). In addition, we observed a significant association between genetically predicted BMI and VTE (OR = 1.59, 95% CI 1.30-1.93 per standard deviation increase in BMI, P = 5.8 × 10). Our study provides evidence for a causal relationship between high BMI and risk of VTE. Reducing obesity levels will likely result in lower incidence in VTE.
Keywords: Adult; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Incidence; Logistic Models; Male; Mendelian Randomization Analysis; Obesity; Polymorphism, Single Nucleotide; Proportional Hazards Models; Venous Thromboembolism